Divergent Roles of Interferon-γ and Innate Lymphoid Cells in Innate and Adaptive Immune Cell-Mediated Intestinal Inflammation - Brasseit, Jennifer; Kwong Chung, Cheong K. C.; Noti, Mario; Zysset, Daniel; Hoheisel-Dickgreber, Nina; Genitsch, Vera; Corazza, Nadia; Mueller, Christoph (Frontiers in Immunology, 2018)
Aberrant interferon gamma (IFNγ) expression is associated with the pathogenesis of numerous autoimmune- and inflammatory disorders, including inflammatory bowel diseases (IBD). However, the requirement of IFNγ for the pathogenesis of chronic intestinal inflammation remains controversial. The aim of this study was thus to investigate the role of IFNγ in experimental mouse models of innate and adaptive immune-cell mediated intestinal inflammation using genetically and microbiota stabilized hosts. While we find that IFNγ drives acute intestinal inflammation in the anti-CD40 colitis model in an innate lymphoid cell (ILC)-dependent manner, IFNγ secreted by both transferred CD4 T cells and/or cells of the lymphopenic Rag1-/- recipient mice was dispensable for CD4 T cell mediated colitis. In the absence of IFNγ, intestinal inflammation in CD4 T cell recipient mice was associated with enhanced IL17 responses; consequently, targeting IL17 signaling in IFNγ-deficient mice reduced T cell-mediated colitis. Intriguingly, in contrast to the anti-CD40 model of colitis, depletion of ILCs in the Rag1-/- recipients of colitogenic CD4 T cells did not prevent induction of colonic inflammation. Together, our findings demonstrate that IFNγ represents an essential, or a redundant, pro-inflammatory cytokine for the induction of intestinal inflammation, depending on the experimental mouse model used and on the nature of the critical disease inducing immune cell populations involved.